The Effect Of Giving Luffa Acutangula Juice On Reducing Cholesterol Levels In The Elderly In Jatiimakmur Village, Pondok Gede Sub-District, Bekasi City, 2022 - Deni Septianida; Omega DR Year (Pusat Riset dan Inovasi Nasional, 2023)
Cholesterol is a soft fatty compound like wax (wax). Most of the body's cholesterol needs are produced by the liver, while hypercholesterolemia (hyper: high, -emia: blood) is a disorder of the fat content in the blood. The prevalence of heart disease in West Java Province based on a doctor's diagnosis is caused by hypercholesterolemia in the population according to characteristics aged 55-64 years by 3.9%, namely as many as 83,251 people. Objective: Is to determine the effect of giving luffa acutangula juice on cholesterol levels in the elderly in Jatimakmur Village, Pondok Ge District, Bekasi City in 2022. Methods: Type of quantitative analytical research, one group pretest posttest design. The study population was all elderly aged > 60 years in Jatimakmur Village, Pondok Gede sub-district, Bekasi City and a sample of 27 people. Univariate, bivariate data analysis. Results: The results of the analysis of the various means showed that the condition of cholesterol levels in elderly respondents who received luffa acutangula juice/oyong therapy decreased by106,370 with a p value < 0.05, namely 0.00. Based on the above data that at 95% there is an effect of giving luffa acutangula juice on reducing cholesterol levels in the elderly. Suggestion: It is hoped that health workers will be able to provide information to patients who have high cholesterol levels (hypercholesterolemia) that they can consume luffa acutangula juice/oyong at the right dosage and the right way to reduce high cholesterol levels (hypercholesterolemia) in the elderly.